Drug permeation across the skin accompanied by enzymatic metabolism - Yamada, Kayoko; Tojo, Kakuji; Hikima, Tomohiro; Yamashita, Akihiro (Drug Delivery System, 1992)
Percutaneus absorption of a drug with enzymatic metabolism in the hairless mouse skin was demonstrated using an in vitro skin permeation apparatus. Prednisolone(PN)and its prodrug, Prednisolone 21- (2E, 6E-Farnesirate)(PNF), were seleced as model drugs. Either intact skin or stripped skin, from which the stratum corneum removed completely, was mounted between the half cells of in vitro skin permeation system. Percutaneous absorption of PN was found to be controlled by permeation in the stratum corneum. The appearance rate of the metabolite(PN)was controlled by the rate of metabolism of PNF in the viable skin rather than by the permeation rate in the stratum corneum. Permeation profiles of PNF for the stripped skin were analyzed by a diffusion model accompanied by enzymatic reaction ; the rate constant of enzymatic reaction was determined to be 0.87 hr-1. The caluculated profiles for PN in donor and receptor solutions well agreed with the experimental results.